INNOVATION OF MUSHROOM NUGGETS FORTIFIED MORINGA LEAVES AS ANTIOXIDANT SOURCE - Pangastuti, Kharisma Diani; Khastini, Rida Oktorida; Hendriyani, Mila Ermila; Murni, Dewi (BIOMA : Jurnal Ilmiah Biologi, 2024)
This study aims to determine the effect of the type of mushroom on the product quality of mushroom nuggets fortified with moringa leaves with organoleptic and chemical parameters and to determine the level of antioxidant activity. This study used a completely randomized design (CRD) with one treatment factor (type of mushroom). The mushrooms used are oyster mushrooms, straw mushrooms, and enoki mushrooms. The result showed that all samples of mushroom nuggets were acceptable to the panelists, with levels of preference ranging from neutral to favorable. Mushroom nuggets fortified with Moringa leaves have a protein content of 14.90-15.51% and a fat content of 8.78-9.68%. The results of the data analysis showed that the control nuggets were significantly different from all the nuggets treated with different types of mushrooms in the parameters of aroma, taste, and texture. However, the treatment of the nuggets with different types of mushrooms did not show significant differences in the parameters of aroma, taste, and texture. The effects of different types of mushrooms on the protein and fat content of the nuggets were not significant (p > 0.05). The IC50 value of the antioxidant activity of mushroom nuggets fortified with Moringa leaves ranged from 5,500 ppm–34,547 ppm, with a very active category.